Problem zaniku niemieckich leksemów na obszarze kaszubszczyzny środkowej - Jeszke, Jerzy (Slavia Occidentalis, 2022)
The material basis of the article consists of words of German origin derived from Standard German: 126 nouns and 15 words representing other parts of speech. In addition, the author includes 13 words of Lower German origin. Today, these words are no longer a part of oral communication or are used rarely (idiolectally).